Twins [videorecording (DVD)] - Reitman, Ivan; Schwarzenegger, Arnold; DeVito, Danny; Preston, Kelly; Bartlett, Bonnie, 1929- (Universal Home Video, 1998)
An ambitious genetic experiment takes the wrong turn when twins -- who look nothing alike -- are born and then separated. Years later the unlikely siblings meet.